Letter: diet‐responsive or just diet‐adherent in eosinophilic oesophagitis. Where is the dietitian?. Issue 4 (29th January 2023) - Fitzpatrick, Jessica A.; Halmos, Emma P.
LINKED CONTENT: This article is linked to Wang et al papers. To view these articles, visit https://doi.org/10.1111/apt.17221 and https://doi.org/10.1111/apt.17350